1994
DOI: 10.1111/j.1365-2885.1994.tb00520.x
|View full text |Cite
|
Sign up to set email alerts
|

A field evaluation of the efficacy of tolfenamic acid and oxytetracycline in the treatment of bovine respiratory disease

Abstract: In a blinded multicentre trial 313 cattle showing clinical signs of respiratory disease were allocated randomly into three groups, treated intramuscularly with a long-acting oxytetracycline formulation at a dose rate of 20 mg/kg bodyweight in combination with vehicle alone (placebo) or with tolfenamic acid at 2 mg/kg bodyweight once or on two occasions with a 48-h interdosing interval. The clinical status of the animals was monitored for 5 days using a specific scoring system and weight gain was calculated bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 4 publications
0
25
0
1
Order By: Relevance
“…In early field studies, usually with small animal numbers, oxytetracycline was reported as effective for metaphylaxis and therapy in cases of calf pneumonia, as assessed by resolution or improvement of clinical signs (Deleforge, Thomas, Davot, & Boisrame, ; Laven & Andrews, ; Morck et al., ; Musser, Mechor, Grohn, Dubovi, & Shin, ). On the other hand, O'Connor et al.…”
Section: Discussionmentioning
confidence: 99%
“…In early field studies, usually with small animal numbers, oxytetracycline was reported as effective for metaphylaxis and therapy in cases of calf pneumonia, as assessed by resolution or improvement of clinical signs (Deleforge, Thomas, Davot, & Boisrame, ; Laven & Andrews, ; Morck et al., ; Musser, Mechor, Grohn, Dubovi, & Shin, ). On the other hand, O'Connor et al.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the absence of such a benefi t is not evidence that NSAID are of no benefi t in the treatment of lameness. Tolfenamic acid has proven analgesic and antiinfl ammatory effects in cattle (Deleforge et al 1994;Landoni et al 1995) but our fi rst measurement of nociceptive threshold was made 72 hours after the injection of tolfenamic acid, 24 hours longer than the dosage interval recommended in the product datasheet (Ethical Agents Ltd). Further research is required to quantify the short-term benefi ts of treating lame cattle with NSAID; in particular, data are needed on whether different products have signifi cantly different benefi ts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, its anti‐inflammatory, antipyretic and antihyperalgesic properties provide a pharmacological basis for its use in combination with antimicrobial drugs, in pneumonias of young calves and pigs. For example, TA has been used for BRD therapy in combination with oxytetracycline (Deleforge et al. , 1994).…”
Section: Introductionmentioning
confidence: 99%